(untitled) (UUM Journal of Legal Studies, 2020)
This paper contributes significantly through suggestions to overcome the problem created by the disastrous US drone strikes in Pakistan. This paper evaluates incidences of the United States’ combat drone strikes in Pakistan and the damage caused to innocent people. It seeks to determine possible violations of international laws and the extent to which these strikes diminish the sovereignty of Pakistan. After the incident of 9/11, the use of combat drones in armed conflicts among states, non-state actors, disruptive groups and organisations has increased and expanded. Combat drones are controlled by operators who depend for their primary sources of information on cameras and sensors to determine their targets. Drone strikes lack identification processes causing many innocent people to be killed or injured. Drone strikes launched in non-conflict areas also increase the concerns about illegitimate interference in a state’s territorial sovereignty and violations of international laws. It covers the following questions. What are the basic principles about the use of force? What kinds of damages are caused by US drone strikes in Pakistan that violate basic human rights principles? What are the concerns of international organisations about drone strikes in Pakistan? Summarily, it covers the United States unlawful drone strikes in Pakistan and damages caused to humanity. The paper uses doctrinal qualitative analysis to situate the research within the ethical, legal and social parameters of the related statutes of international law. The research methodology adopted is evaluative, interpretive and analytical. The paper consists of 8 segments: (1) drones and the United States armed forces, (2) some basic international law principles about the use of force, (3) possible human rights violations, (4) US drone strikes diminish the sovereignty of Pakistan, (5) demands for transparency, (6) the damages caused to humanity by the drone strikes, (7) concerns of international organisations about illegitimate drone strikes causing extra judicial killings and (8) some recommendations to regulate the use of combat drones. It demonstrates that international law does not regulate the use of combat drones in armed conflict and no considerable effort has been made to bring the use of combat drones under the rule of law. Furthermore, US drone strikes in Pakistan’s territory have been done without consensus, resulting in the violation of Pakistan’s sovereignty and the killing of innocent people.